Recent Advances in Zinc Complexes for Stereoselective Ring-Opening Polymerization and Copolymerization - Xia Li; Yang Li; Gangqiang Zhang; Yat-Ming So; Yu Pan (Inorganics)
Recent advances in zinc complexes for stereoselective ring-opening polymerization (ROP) and copolymerization (ROCOP) highlight their pivotal role in synthesizing biodegradable aliphatic polyesters and polycarbonates. These materials address the urgent demand for sustainable alternatives to petroleum-based plastics, with stereochemical control directly impacting polymer crystallinity, thermal stability, and degradability. Zinc catalysts, leveraging low toxicity and versatile coordination chemistry, enable precise stereoregulation, whose performance is modulated by ligand steric/electronic effects, coordination geometry, and reaction conditions. This review summarizes the recent developments in zinc complexes for stereoselective ROP and ROCOP, focusing on ligand design strategies to enhance catalytic performance.